The Return-to-Sport Clearance Continuum Is a Novel Approach Toward Return to Sport and Performance for the Professional Athlete - Pete Draovitch, D.P.T., S.C.S; Snehal Patel, M.P.T., S.C.S; William Marrone, D.P.T., S.C.S; M. Jake Grundstein, D.P.T, M.B.A; Reg Grant, C.A.T (C); Adam Virgile, M.S., C.S.C.S; Tom Myslinski; Asheesh Bedi, M.D; James P. Bradley, M.D; Riley J. Williams, III, M.D; Bryan Kelly, M.D; Kristofer Jones, M.D (Elsevier, 2022)
The concept of returning to sport for a professional athlete is still under debate for the professional athlete in today's sports environment. It is critical for the professional athlete to be able to return to sport at a highly competitive level but also to return in a safe and timely measure. With no "gold standard" of sport testing, it is difficult to determine what the right progression or testing regimen should be. The Return to Sport Clearance Continuum does not look at one moment in time, but looks throughout the continuum of healing to determine readiness for sport. The purpose of this article is to explore the concept of RTS being part of an evolving continuum rather than the traditional notion that RTS is a single decision made at a discrete point in time. The principles of progressive but regular testing procedures including qualitative and quantitative movement are presented to help the professional athlete return to sport at their maximal performance level. Level of Evidence: V, expert opinion.